Plano Nacional de Educação e as tecnologias da informação e comunicação: trajetória e desafios para a formação dos jovens da educação básica - Daniela da Costa Britto Pereira Lima; Tatiane Custódio da Silva Batista (EccoS – Revista Científica)
The aim of this study is to present and analyze how information and communication technologies (TIC) are treated in official documents governing education in Brazil, culminating in the National Education Plan (PNE) in force ( 2014 - 2024 ). For this, it was made a documentary and bibliographic research on education and technologies in the basic education, presenting public policies and concepts developed in this regard. As a result, it is emphasized that in the annex of the law that deals with the PNE ( 2001 - 2011 ), the technologies are mostly related to distance education, while in the annex of the law that deals with the PNE ( 2014 - 2024 ) they are presented in various parts, sometimes related with distance education with assistive technologies and technologies in the school environment. It is noteworthy that both plans recognize and promote the training of teachers for the pedagogical use of technologies in the school environment.